2021
DOI: 10.1177/02537176211021785
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Long-Term Care Homes for Older Adults in India

Abstract: The rising aging population in India has led to an increased caregiving burden, and accordingly, the number of residential care facilities is also burgeoning. There is no regulatory framework or registration authority specifically for residential care homes in India. The article’s objective is to understand the need for a regulatory framework in India in the context of historic and global experiences in the UK, USA, and Europe. Although there is a lack of literature comparing the community home-based care and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…These model guidelines focus on services and physical aspects of the environment rather than the quality of care. The authors are fairly confident that the types of human rights violations observed in this study, would be found elsewhere in India (see also, [ 41 ]). As Tamil Nadu was the first state to introduce a set of Minimum Standards for old age homes in 2016, one may expect provision in this state to be ‘better’ than elsewhere as the standards have become embedded into practice over time.…”
Section: Discussionsupporting
confidence: 58%
“…These model guidelines focus on services and physical aspects of the environment rather than the quality of care. The authors are fairly confident that the types of human rights violations observed in this study, would be found elsewhere in India (see also, [ 41 ]). As Tamil Nadu was the first state to introduce a set of Minimum Standards for old age homes in 2016, one may expect provision in this state to be ‘better’ than elsewhere as the standards have become embedded into practice over time.…”
Section: Discussionsupporting
confidence: 58%
“…However, the adequate implementation of these provisions is a matter of concern. There is a paucity of formal mechanisms in terms of feedback, appraisal, complaints or grievance redressal, that makes it difficult for ensuring the overall well-being of older adults residing in old-age homes [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few formal LTC services such as old‐age homes, day care centres, residential facilities and domiciliary care services are available, and these services are predominantly provided by private and not‐for‐profit organizations, although a few public facilities also exist (Rajagopalan et al, 2020). Currently, care homes and residential facilities are largely unregulated, with limited data available on their numbers and characteristics (Harbishettar et al, 2021). Some publicly supported LTC services exist, but these are scanty and fragmented under the auspices of multiple government programmes, such as the Integrated Programme for Older Persons, National Programme for Healthcare of Elderly, National Mental Health Programme, and National Programme for Palliative Care (Scheil‐Adlung, 2015).…”
Section: Current Ltc Landscape In Lmics: a Supply Side Assessmentmentioning
confidence: 99%